Alcohol consumption among college students in Minahasa, Indonesia: a cross-sectional study towards the formulation of intervention strategies - Supit, Alva; Mamuaja, Prycilia; Pissu, Aditya (International Journal Of Community Medicine And Public Health, 2017)
Background: College students are within the high-risk group to experience the full spectrum of alcohol-related psychopathologies, ranging from initial contact with alcohol to the severe problematic drinking. The prevalence, degree of severity, reasons of drinking, among other variables, however, have been inconsistent across studies. Therefore, it is crucial to replicate such studies in different socio-cultural settings to synthesize a broader understanding about alcohol-consuming behavior and formulating intervention strategies. This research aims to describe the pattern of alcohol drinking behavior among college students in Minahasa, Indonesia, and to analyze its correlation with academic performance. Methods: We conducted a questionnaire-based cross-sectional study to investigate the alcohol-consumption pattern and examined its association with the students' academic performance obtained from the campus database. A total-sampling technique was applied to draw the samples. Chi-square and Kendall's tau analyses were employed accordingly to measure the relationship significance. Results: From 417 samples (338 samples were females), 70.98% of them reported never had consumed alcohol of any amount. Male sex and local ethnicity are positively associated with consuming behavior. We found an association between alcohol consumption status with cumulative GPA but not with current GPA. Although alcohol consumers considered GPA as less important, the self-insight about their academic performance is intact. The consumed beverages were mostly beers, followed by traditional liquor and winepalms. Most of them consumed alcohol to "warm-up the body"—a common practice in this area, followed by social reasons. Only small number of them identified themselves as being addicted. Majority of the consumers realized the importance to reduce or quit consuming alcohol. The implications of these findings are then discussed. Conclusions: This study showed that most of the students have never consumed alcohol. However, among the consumers, male sex and local ethnicity are more prone to become alcohol users. The academic performance is also affected, and since most of the consumers consider to reduce their drinking behavior, professional interventions are necessary to facilitate recovery attempts.